Dinasti Politik dalam Kontestasi Pemilihan Kepala Daerah di Indonesia - Yohanes Lado Jera; Achmad Edi Subiyanto; Markoni Markoni Markoni (Syntax Idea, 2022)
In this study is to describe the political dynasty in the regional head election competition in Indonesia. This study was conducted because of the reality of political dynasties that occur in Indonesian society that continues to increase from year to year. This research was born from the decision of the Constitutional Court Number 33/PUU-XIII/2015 which legalized the practice of political dynasties in the nomination of regional heads. This study aims to explain that political dynasty is an empirical, juridical reality and is a consequence of the rule of law that must create justice, especially in the process of nominating regional heads and deputy regional heads in accordance with applicable law. The formulation of the problem is first, Is the political dynasty in the election of regional heads contrary to human rights guaranteed by the 1945 Constitution of the Republic of Indonesia? Second, What is the constitutionality of political dynasties in the Election of Regional Heads in Indonesia? The research method used is a type of normative law research conducted by reviewing library materials or secondary materials. Normative research aims to systematize, correct and clarify the rules of law that apply to a particular field of law by analyzing the texts on primary and secondary legal materials and then analyzed. The results show that the political dynasty as a reality of the election of regional heads is constitutional because it does not conflict with the 1945 Constitution and the Human Rights Law. Second, there is a need to be regulated in the Law on the regulation of the election of regional heads and stricter requirements of candidate competence, than the requirements of intellectual, and managerial leadership skills, experience, and morality. This aims to find out how integrity the candidate is.